2015
DOI: 10.1111/bph.13093
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term variability in QT interval and ventricular arrhythmias induced by dofetilide are dependent on high‐frequency autonomic oscillations

Abstract: Background and PurposeThe present study was undertaken to investigate an effect of dofetilide, a potent arrhythmic blocker of the voltage-gated K+ channel, hERG, on cardiac autonomic control. Combined with effects on ardiomyocytes, these properties could influence its arrhythmic potency.Experimental ApproachThe short-term variability of beat-to-beat QT interval (STVQT), induced by dofetilide is a strong surrogate of Torsades de pointes liability. Involvement of autonomic modulation in STVQT was investigated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…The increased propensity for torsade de pointes upon dofetilide treatment could be partially accounted for by the increased beat‐to‐beat APD (and QT interval) variability, which fully complies with the TRIaD concept (see Section for discussion).…”
Section: Arrhythmogenic Responses To Antiarrhythmic Drugsmentioning
confidence: 56%
“…The increased propensity for torsade de pointes upon dofetilide treatment could be partially accounted for by the increased beat‐to‐beat APD (and QT interval) variability, which fully complies with the TRIaD concept (see Section for discussion).…”
Section: Arrhythmogenic Responses To Antiarrhythmic Drugsmentioning
confidence: 56%
“…Alternatively, the autonomic nervous system has been reported to play a critical role in ventricular arrhythmia liability of drugs, causing QT prolongation through abnormalities in the restoration of the QT/RR relationship (Fossa, ). In a recent study, we showed that the autonomic high‐frequency (HF) oscillations in the amplitude of heart rate (HR) play a major role in beat‐to‐beat variability of ventricular repolarisation (BVR) and are one of the mechanisms responsible for dofetilide‐induced TdP (Champeroux et al , ). These HF oscillations result from alternate sequences of parasympathetic activation and deactivation occurring within a very short period of a few seconds (Pagani et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…This is why the hERG assay is a regulatory test in drug development17. However, all drugs blocking the hERG channel are not systematically associated with TdP, suggesting that I KR blockade and QT prolongation are insufficient to trigger TdP18. However, the fact that some I KR inhibitors are torsadogenic has slowed the development of promising new drugs1920.…”
mentioning
confidence: 99%